Penamaan Semantis dan Pandangan Budaya pada Jajanan Pasar Jawa Barat - Ahmad Maulana Ghufar; Suhandano Suhandano (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This research aims to describe the semantic classification of the names of West Java street foods and to reveal cultural views that are represented through the names of West Java street foods. The theory used in this research is the naming theory proposed by Chaer (2009) and the ethnosemantic theory presented by Baehaqie (2017). A descriptive qualitative approach was used in this research with two types of data: written and oral. Listening and speaking methods were used to obtain the data. The data were analysed using the referential equivalent method with the basic technique of comparison and the advanced technique of equalizing comparison (HBS). Data analysis in this research uses an ethnosemantic approach. Formal and informal methods were used to present the data. The result of this research shows that the semantic naming of West Java street foods has varied classifications, including (a) mention of distinctive characteristics, (b) inventor and creator, (c) place of origin, (d) ingredients, (e) similarity, (f) shortening, and (g) new naming. Furthermore, West Java street foods have three functions from a cultural point of view. Those three functions are the enjoyment function, social function, and ritual function.